Competition on the fast lane: The price structure of homogeneous retail gasoline stations - Alex Korff (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
This paper studies the relationship between retail gasoline pricing strategies and potential demand. Utilising detailed data on traffic on the German Autobahn and the special case of Bundesautobahntankstellen, the interaction between demand and price competition is studied, as are the changes in competition intensity across distances and road networks. The observed relationships match an Edgeworth cycling behaviour, whose steps appear to be determined by the changes in demand. Cycling intensity and undercutting increase with traffic, while relenting phases are timed to substantial changes in traffic ows. Thus, competition is found to intensify with rising potential demand, as that increases the incentives of undercutting.
Keywords: D22; D40; L11; L81; R12; 330; Retail gasoline prices; Edgeworth Cycles; Regional Infrastructure; Price Competition